Was Jesus of Nazareth a Monotheist? Conversation with Cultural Studies. (August 2019) - Neyrey, Jerome H.
Did Jesus of Nazareth, born of a woman and born under the law, confess the Shema like all other Israelites? Was he a monotheist? Although scholarship argues that there were many types of monotheism, we focus here on strict Israelite monotheism (Deut 6:4). What does Jesus have to say for himself? This article does not go over plowed ground, but seeks to add to the conversation the use of two social science models: understanding "role" and "status, " and interpreting data in terms of the relationships of Patron-broker-client. These models necessarily serve to clarify much scholarship on monotheism, as well as clarify for us whether people worshiped Christ or prayed to him. In short, Jesus always functioned in two roles, either as God's client or as broker between God-Patron and Israel-client. Paul and other NT authors always put him in this place, namely, in a client or broker role, who never encroached on God's uniqueness or sovereignty.